Enhanced vibrating particles system algorithm for damage identification of truss structures - Kaveh, A; Vaez, S R Hoseini; Hosseini, P (Scientia Iranica, 2019)
Vibrating Particles System (VPS) optimization is a recently developed metaheuristic algorithm for optimization. This algorithm is inspired by the free vibration of freedom systems' single degree with viscous damping. In this method, each answer is modeled as a particle that moves to its equilibrium position; new positions of the vibrating particle system are updated according to a historically best position. Enhanced Vibrating Particles System (EVPS) uses new approaches to improve the performance of the VPS algorithm. In this study, a dynamic method and modal based approach consisting of natural frequencies and mode shapes are used in the objective function formulation. To demonstrate the performance of the VPS and EVPS, different truss structures including several multiple elements scenarios with noise and without noise in modal data are considered for detecting damage problems. Additionally, all scenarios are studied with significant mutations. Results show that the EVPS algorithm has reached better answer than the VPS algorithm for damage detection problems.